INVESTIGATION OF ROCK DEFORMATION PROPERTIES IN TERMS OF THE NONLINEAR ACOUSTIC PARAMETER - Zinov'yeva G.P.; Nesterov I.I.; Zhdakhin Ye.L.; Artma E.E.; Gorbunov Yu.V. (My University, 1989)
Analysis of rock deformation is one of the central problems of theoretical and applied geology and geophysics. The stress states of rocks in nature are well modeled by experiments in high-pressure chambers on rock specimens of representative dimensions. At low stress levels the elastic deformation is governed primarily by the real texture and composition of the rock and by the type of bonding between its phases. The present paper demonstrates that in investigations of the deformation properties of rocks of various textural and structural types, the nonlinear acoustic parameters is an order of magnitude more sensitive than such acoustic characteristics commonly used in geophysics as longitudinal and transverse acoustic wave velocities.